Study protocol of a multicenter, randomized, non-inferiority, open-label study investigating the efficacy of a fixed-dose combination regimen of dapagliflozin/metformin versus co-administered dual therapy based on glycemic control, satisfaction and adherence in patients with newly diagnosed type 2 diabetes mellitus - Wang, Jiaxuan; Wei, Ying; Shi, Ping; Chen, Ji; Xu, Lingling; Kong, Yinghong; Ye, Jun; Wang, Xueqin; Xu, Juan; Wang, Guang (Frontiers in Endocrinology, 2025)
IntroductionThe combination of dapagliflozin and metformin is commonly used as an initial therapy for patients with type 2 diabetes mellitus (T2DM) with high glycated hemoglobin (HbA1c) levels. Although bioequivalence has been established for the fixed-dose combination (FDC) of dapagliflozin/metformin extended-release (XR) compared to the co-administration of dapagliflozin and metformin XR, it remains uncertain whether the efficacy of dapagliflozin/metformin FDC is comparable to that of co-administration. Additionally, it is still unclear whether fixed-dose combinations offer advantages in terms of patient adherence and satisfaction. This study aims to compare the dapagliflozin/metformin XR FDC with co-administration of dapagliflozin and metformin XR for efficacy in terms of glycemic control, patient satisfaction, quality of life and adherence in Chinese patients with newly diagnosed T2DM.Methods and analysisThis multicenter, randomized, non-inferiority, open-label clinical trial enrolled 632 patients with T2DM (HbA1c 7.5–10%) in 35 research centers in China. After enrollment, the patients will be randomly assigned to receive either FDC treatment (10 mg dapagliflozin and 1000 mg metformin XR) or co-administered 10 mg dapagliflozin and 1000 mg metformin XR tablets for 24 weeks. The primary endpoint was the change in HbA1c level from baseline after 24 weeks of treatment. Secondary endpoints included the proportion of patients achieving HbA1c below 7.0%, absolute changes in fasting plasma glucose and postprandial glucose from baseline to week 24, the difference in patient satisfaction measured with the diabetes treatment satisfaction questionnaire, medication usage measured with adherence to refills and medications scale for diabetes between the two groups at week 24, change from baseline in diabetes quality of life questionnaire score at week 12 and week 24, and safety. Continuous glucose monitoring will also be used to evaluate the benefits of FDC compared with co-administration on glycemic variability.DiscussionThis study, as the first of its kind, will provide comparative data on the efficacy of the dapagliflozin/metformin XR FDC and co-administration of dapagliflozin and metformin XR in terms of glycemic control, patient satisfaction, quality of life and adherence. These data will help clinicians make more informed decisions for patients with type 2 diabetes and may improve medication burden, treatment adherence, and satisfaction.